Disc-jet coupling in the 2009 outburst of the black hole candidate H1743-322 - Miller-Jones, James; Sivakoff, G.; Altamirano, D.; Coriat, M.; Corbel, S.; Dhawan, V.; Krimm, H.; Remillard, R.; Rupen, M.; Russell, D.; Fender, R.; Heinz, S.; et al. (Wiley-Blackwell Publishing Ltd., 2012)
We present an intensive radio and X-ray monitoring campaign on the 2009 outburst of the Galactic black hole candidate X-ray binary H1743-322. With the high angular resolution of the Very Long Baseline Array, we resolve the jet ejection event and measure the proper motions of the jet ejecta relative to the position of the compact core jets detected at the beginning of the outburst. This allows us to accurately couple the moment when the jet ejection event occurred with X-ray spectral and timing signatures. We find that X-ray timing signatures are the best diagnostic of the jet ejection event in this outburst, which occurred as the X-ray variability began to decrease and the Type C quasi-periodic oscillations disappeared from the X-ray power density spectrum. However, this sequence of events does not appear to be replicated in all black hole X-ray binary outbursts, even within an individual source. In our observations of H1743-322, the ejection was contemporaneous with a quenching of the radio emission, prior to the start of the major radio flare. This contradicts previous assumptions that the onset of the radio flare marks the moment of ejection. The jet speed appears to vary between outbursts, with a possible positive correlation with outburst luminosity. The compact core radio jet reactivated on transition to the hard intermediate state at the end of the outburst, and not when the source reached the low hard spectral state. Comparison with the known near-infrared behaviour of the compact jets suggests a gradual evolution of the compact jet power over a few days near the beginning and end of an outburst.